Shape Control of VO2 (B) Hierarchical Nanostructures1. Issue 10 (14th May 2014) - Ji, Qi; Jiang, Yingchang; Zhang, Zhongping; Tian, Yongtao; Wang, Zhenyang
Abstract A green route is designed to gain a clear idea of growth mechanism of complex VO2 (B) hierarchical microstructures, since this kind of metal oxide has various metastable phases due to their diverse valence states. Three‐dimensional (3D) uniform flower‐like VO2 (B) hierarchical microstructure has thus been assembled with the interleaving nanoplates, which are about 25 nm in thickness and well‐crystallized in structure with {114} planes as the dominant surfaces. Results of the systemic control experiments revealed that formation of the flower‐like VO2 (B) results from a fast nucleation‐growth process, where ethylene glycol (EG) not only acts as a green solvent and reductive agent, but also plays a key role in self‐assembly of the resulted VO2 (B) hierarchical microstructures. Hydroxyl amount on the solvent molecule is crucial in formation and shape control of VO2 (B) hierarchical microstructures. Result of this work would be helpful to understand the growth mechanism of complex three‐dimensional hierarchical superstructures of different metal oxides, which is very important to material science and inorganic synthetic chemistry.